ASSURANCE OF LEGALITY AND VALIDITY OF THE PROCEDURAL DECISIONS MADE BY THE INVESTIGATOR IN CRIMINAL PROCEEDING - Sumbarova, Marina (Administrative and Criminal Justice, 2015)
One of participants of criminal trial – the persons directing process, according to the Criminal procedure law (CPL) existing now in Latvia is the investigator. According to point 1 of part 2 of article 29 CPL, it has rights in the order established by the law to make any procedural decision and to make any procedural action or to charge its production to participants of an investigation team or the performer of procedural instructions. In article the author investigates conceptual essence of criminal procedure decisions, the legal characteristic of the resolution of the investigator, decision-making in the form of resolutions on the beginning of criminal trial, refusal to begin criminal trial, and also the resolutions directed on collecting and fixing of proofs in criminal trial and other resolutions. Making procedural decisions is a guarantee of high-quality investigation of criminal trials and observance of the rights of its participants.